The Purchase Intention and Brand Equity in Co-Branding Indomie Rasa Chitato Sapi Panggang - Grace Putlia (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2020)
Food producers have a new challenge in this era, where producers are challenged to be able to offer a variety of products if they still want to exist in the midst of fierce competition. The phenomenon also seems clear that many brands collaborate and then launch new products. One of them is that some time ago Indofood released its Indomie Hype Abis Goreng Rasa Chitato Sapi Panggang.Qualitative research with case study design gets answers to existing research problems after successfully conducting data processing from 27 informants who meet the criteria. The answer to research issue 1 is that Indomie's purchase intention and brand equity Indomie rasa Chitato Sapi Panggang resulting from co-branding is very good from the viewpoint of the community. Also answered research problem 2 is that the co-branding of the two well-known brands can be a guarantee of new products that are sure to succeed in the market. The difference lies in the reason, namely: succeed in the market for a long period of time or just a trend, because a new thing will always attract attention either through purchase intention or brand equity. But the survival time in the market must not be spared.